Successful control of recurrent angiosarcoma in the external auditory canal with CyberKnife radiosurgery and bisphosphonate risedronate sodium - Eimei Iwama; Taku Fujimura; Akira Hashimoto; Yukikazu Numata; Takahiro Haga; Setsuya Aiba (Wolters Kluwer Medknow Publications, 2015)
Angiosarcoma (AS) is a highly aggressive vascular tumor that spreads widely throughout the skin. Since AS tends to recur locally and metastasize early, an additional intensive therapy is necessary. In this report, we describe an 83-year-old man with recurrent AS that metastasized to the right external auditory meatus, who achieved complete remission with CyberKnife and weekly administration of bisphosphonate risedronate sodium. Results of the present study might suggest the novel possibility of using CyberKnife with weekly administration of bisphosphonate risedronate sodium for the treatment of inoperable metastatic AS.